Zakat and Green Economic Growth from a Maqashid Sharia Perspective - Bianda, Ryan (Center of Strategic Studies (PUSKAS) BAZNAS, 2025)
This study investigates the role of zakat in advancing green economic growth through the normative lens of Maqashid Sharia. The objective is to evaluate how zakat, beyond its redistributive function, can foster sustainable development by integrating economic empowerment, social welfare, and environmental stewardship.A qualitative approach was applied, drawing on systematic literature review and conceptual analysis. Data were sourced from academic research, institutional reports, and policy documents on zakat, green economy, and sustainability. The analysis focused on zakat as the independent fiscal instrument, green economic growth as the dependent outcome, and Maqashid Sharia as the guiding framework. The findings demonstrate that zakat significantly contributes to inclusive growth when aligned with sustainable development strategies. In Malaysia and Indonesia, zakat has alleviated poverty, strengthened financial inclusion, and empowered marginalized groups. When guided by Maqashid principles, zakat also shows potential to support eco-friendly enterprises, renewable energy, and conservation programs. Nevertheless, limited regulations, low literacy on productive zakat, and weak institutional collaboration constrain its impact. Opportunities for digital innovation and cross-sectoral partnerships, however, provide viable pathways for zakat to be institutionalized as a green economic driver. This study concludes that zakat, integrated with Maqashid Sharia, can balance economic, social, and ecological objectives, positioning it as a strategic instrument for green economic transformation and long-term sustainability.